Impact of Nitrogen Sparging on Chemical and Sensory Characteristics of Verdejo and Sauvignon blanc Wines - del Barrio-Galán Rubén; del Alamo-Sanza Maria; Martínez-Gil Ana María; González-Lázaro Miriam; Nevares Ignacio (Foods)
Sparging is a common technique in wineries that consists of injecting a gas, normally before bottling, in order to displace the dissolved oxygen in the wine and prevent oxidation. The objective of this study was to examine the effect of sparging on wines with three different levels of dissolved oxygen and the evolution of the chemical parameters in a bottle. This study was carried out on two white wines, Verdejo and Sauvignon blanc. The results indicated that sparging did not immediately affect the chemical parameters in the white wines, but it did affect their evolution in bottles, with a greater effect found in the Sauvignon blanc wines than in the Verdejo wines. Sparging, which was carried out to remove oxygen from the wines, had a protective effect on their color during the time in the bottles, preventing a more rapid decrease in free SO2. The effect of sparging on the volatile compounds of the wines was more evident in the Sauvignon blanc wines, which showed a reduction in their content, possibly due to carry-over when the N2 was applied. With regard to the effect of sparging on the sensory profile of the wines, no immediate effect was found. However, the wines with a DO content of 6 and 8.4 mg/L to which sparging was applied evolved better in the bottles than the deoxygenation wines, showing more fruity notes and fewer oxidized and phenolic aromas (mainly in the Verdejo wines).